Neuromuscular fatigue following a singles badminton match - Lin, Z.; Nosaka, K.; Abbiss, C. R.; Blazevich, A.; Wilkie, J. (World Badminton Federation, 2016)
A typical badminton singles match involves numerous intense and high impact movements. Lunges are believed to induce significant muscle damage following a match. The purpose of this study was to investigate changes in knee extensor neuromuscular function after a simulated 1 hour badminton singles match in relation to the number of lunges performed in the match.